Making Games with Python & Pygame - Sweigart, Al; Open Textbook Library (Open Textbook Library, 2012)
This book will teach you how to make graphical computer games in the Python programming language using the Pygame library.This book assumes you know a little bit about Python or programming in general. If you don't know how to program, you can learn by downloading the free book "Invent Your Own Computer Games with Python" from http://inventwithpython.com. Or you can jump right into this book and mostly pick it up along the way. This book is for the intermediate programmer who has learned what variables and loops are, but now wants to know, "What do actual game programs look like?" There was a long gap after I first learned programming but didn't really know how to use that skill to make something cool. It's my hope that the games in this book will give you enough ideas about how programs work to provide a foundation to implement your own games.
Chapter 1 - Installing Python and Pygame -- Chapter 2 - Pygame Basics -- Chapter 3 - Memory Puzzle -- Chapter 4 - Slide Puzzle -- Chapter 5 - Simulate -- Chapter 6 - Wormy -- Chapter 7 - Tetromino -- Chapter 8 - Squirrel Eat Squirrel -- Chapter 9 - Star Pusher -- Chapter 10 - Four Extra Games
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks